Sosialisasi Penggunaan Sosial Media Untuk Meningkatkan Kegiatan Produktif Bagi Ibu PKK Kelurahan Ganjar Agung - Endang Sri Utami; Ayang Kinasih; Erni Mariana; Siti Qomariyah; Kusuma Wardany; Ummi Rosyidah (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The number of internet users in Indonesia continues to increase every year, but the increase in the number of social media users is not accompanied by an increase in people's ability to choose and utilize information safely. Online entrepreneurship has many benefits as it can be done from the comfort of their own home and does not require large capital. The mentoring approach is carried out in two stages. First, a direct inspection was carried out of the participants and the location of the activity. It also covers issues related to participant understanding and other needs. For the second stage, materials must be distributed at the location. Implementation in the field also includes presentations and questions and answers about the material. As a result of this community service activity, PKK mothers will be more adept at using the internet and social media. PKK mothers have learned to use the internet and social media to increase productivity. The field of knowledge will help improve education and culture by providing broader insight and experience about the outside world.